Regulation of intracellular pH in the rabbit cortical collecting tubule. - Weiner, I D (1990)
The cortical collecting tubule (CCT) is an important nephron segment for Na+, K+, water and acid-base transport. Differential loading characteristics of the pH sensitive dye 2',7'-bis-(2-carboxyethyl)-5(and-6)carboxyfluorescein (BCECF) and basolateral Cl- removal were used to identify and study intracellular pH (pHi) regulation in each of three cell types involved in this transport. Both principal cells and beta-intercalated cells were found to have a basolateral Na+/H+ exchanger based on the Na+ and amiloride sensitivity of pHi recovery from acid loads. Intercalated cells demonstrated abrupt pHi changes with basolateral Cl- removal. alpha-intercalated cells alkalinized; beta-intercalated cells acidified. In the beta-intercalated cells, luminal Cl- removal blocked changes in pHi in response to changes in luminal HCO3- or peritubular Cl-, providing direct evidence for a luminal Cl-/HCO3- exchanger. In principal cells, brief removal of either peritubular or luminal Cl- resulted in no change in pHi; however, return of peritubular Cl- after prolonged removal resulted in a rapid fall in pHi consistent with a basolateral Cl-/HCO3- exchanger, which may be relatively inactive under baseline conditions. Therefore, Cl-/HCO3- exchange is present in all three cell types but varies in location and activity.